An Insight Into The Effect Of Mitragyna Speciosa Korth Extract On Various Systems Of The Body - Rani Sakaran; Faizah Othman; Ibrahim Jantan; Zar Chi Thent; Srijit Das (IDOSI Publications, 2024)
Mitragyna speciosa (MS) Korth is a tropical plant which has been widely used by locals for treatment of various diseases. However, the abuse of ketum has gained a lot of attention all over the world. Mitragynine is a major alkaloid of the plant which is widely used as a recreational drug because of its morphine-like properties. Several studies have been conducted based on the effects of MS crude extract and its alkaloid components. Toxicological effects of MS crude extract on experimental animals are still lacking. The present review was an effort to summarize the effects of MS on different systems of the body such as central nervous system, gastrointestinal system and urinary system. Better understanding of the toxicological effects on different organs may help in better diagnosis and treatment.